Gas sensor for detecting NH3, preparation method and application
By growing a Cu3(HHTP)2 metal-organic framework on a laser-induced graphene electrode to form a LIG@Cu3(HHTP)2 composite film, the problems of traditional sensors working at high temperatures and having poor moisture resistance were solved, and the effect of rapid response and highly selective detection of NH3 at room temperature was achieved.
Patent Information
- Application Number
- CN202510801106.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-09-05
AI Technical Summary
Existing metal oxide semiconductor gas sensors require high temperatures when detecting ppm-level NH3, have difficulty distinguishing NH3 from other gases in human exhaled breath, and have poor moisture resistance, limiting their application in wearable devices.
Laser-induced graphene electrodes combined with layer-by-layer self-assembly process were used to grow Cu3(HHTP)2 metal-organic framework on its surface to form LIG@Cu3(HHTP)2 composite film. The flexibility and conductivity of polyimide film and the porous structure of Cu3(HHTP)2 were utilized to improve the adsorption and reaction activity of NH3.
It achieves fast response and recovery at room temperature, highly selectively distinguishes NH3 from other gases, has good stability and moisture resistance, and is suitable for wearable devices.
Smart Images

Figure CN120594627A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas sensor preparation, and in particular relates to a gas sensor for detecting NH3, a preparation method and an application thereof. Background Art
[0002] Ammonia (NH3) is a key biomarker, and exhaled ammonia can be used as a typical biomarker for noninvasive clinical diagnosis (e.g., kidney disease or gastric ulcers). The exhaled ammonia concentration in patients with end-stage renal disease (ESRD) (mean, 4.88 ppm; range, 0.82 to 14.7 ppm) is significantly higher than that in healthy individuals (mean, 0.96 ppm; range, 0.425 to 1.8 ppm). Therefore, the development of highly sensitive and selective ppm-level ammonia detection technology is extremely important for medical diagnosis.
[0003] A gas sensor is a device that converts chemical signals into electrical signals. The key to its performance lies in the choice of materials for the sensitive layer. Traditional metal oxide semiconductor (MOS) gas sensors, such as SnO2, ZnO, and TiO2, typically require high operating temperatures to achieve sufficient sensitivity, which limits their application in wearable and portable sensing devices. Therefore, developing gas sensors that can operate at room temperature is particularly important.
[0004] In non-invasive kidney disease diagnosis, NH3 detection requires high-performance gas sensing materials capable of detecting NH3 concentrations in the ppm range. Furthermore, exhaled breath is a complex mixture containing thousands of gases, and the relative humidity often exceeds 90%. Accurately distinguishing NH3 from other gaseous species and effectively eliminating humidity interference in exhaled breath analysis pose key challenges for gas sensors. These challenges have motivated the development of novel sensing materials with high selectivity and moisture resistance to enable ppm-level NH3 gas detection at room temperature. The sensor exhibits high response, a wide detection range, a low detection limit, high selectivity, and excellent stability. Summary of the Invention
[0005] In response to the above technical problems, the present invention proposes a gas sensor for detecting NH3, a preparation method and an application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention is to provide a method for preparing a gas sensor for detecting NH3, wherein a laser-induced graphene electrode is prepared on a polyimide film, and the laser-induced graphene electrode is alternately immersed in a copper ion solution and an HHTP (2,3,6,7,10,11-hexahydroxytriphenylene) ligand solution. A metal-organic framework is grown on the surface of the laser-induced graphene electrode through a layer-by-layer self-assembly process, and after drying, a gas sensor based on a LIG@Cu3(HHTP)2 composite material film is obtained.
[0008] In the preparation method of the present invention, LIG is prepared by laser direct writing technology, using laser irradiation on a polyimide (PI) film to form interdigitated electrodes. Then, a Cu3(HHTP)2MOF is grown on the LIG surface through a layer-by-layer process, forming a composite material with a hierarchical porous structure. The polyimide film serves as a flexible substrate, exhibiting excellent flexibility and chemical stability. The LIG, acting as a growth platform, provides abundant active sites and good electrical conductivity for the growth of Cu3(HHTP)2. Its macroscopic porous structure facilitates the rapid transport and diffusion of gas molecules, enabling rapid sensor response and recovery. The laser-induced graphene electrode exhibits excellent electrical conductivity and a porous structure. The Cu3(HHTP)2, with its large specific surface area and uniform pore size distribution, enhances its adsorption and reactivity for NH3 molecules. The reason why 2,3,6,7,10,11-hexahydroxytriphenylene was chosen as the ligand is that the metal-organic framework obtained using this ligand has a two-dimensional structure, which can be well combined with 2,3,6,7,10,11-hexahydroxytriphenylene, thereby improving the stability of the sensor.
[0009] As a preference of the present invention, the copper ion concentration in the copper ion-containing solution is 1 mM; and / or the concentration of the HHTP ligand solution is 0.1 mM.
[0010] In the present invention, a low-concentration copper ion solution and a ligand solution are combined with a layer-by-layer self-assembly process to precisely control the loading amount of the metal-organic framework, avoid excessive membrane thickness, and facilitate the generation of a multilayer structure, thereby increasing porosity and the number of reaction sites, thereby improving the detection effect. However, the measure of regulating the loading amount of the metal-organic framework by regulating the concentration of the copper ion solution and the ligand solution is not conducive to the generation of the metal-organic framework on the one hand, and on the other hand, it easily leads to excessive membrane thickness and excessively low porosity, thereby affecting the detection effect.
[0011] Optionally, the copper ion solution is selected from copper acetate solution, which has good water solubility and chemical stability and can provide a stable Cu 2+ ion.
[0012] Optionally, the solvents of the copper ion solution and the HHTP ligand solution are both ethanol, which has good solubility and volatility.
[0013] As a preference of the present invention, the immersion temperature is 50° C.; and / or, in each growth cycle, the immersion time of the copper ion-containing solution and the HHTP ligand solution are 20 min and 40 min, respectively.
[0014] As a preference of the present invention, after each growth cycle, a step of washing with ethanol is further included; and / or the number of times of the alternating immersion is 1 to 6 times.
[0015] Optionally, the drying temperature is 60° C., and the drying time is 12 hours.
[0016] Optionally, the width of the laser-induced graphene electrode is 0.5 mm, and the pitch / width ratio is 1:1.
[0017] Optionally, the preparation method of the laser-induced graphene electrode is: using a pulsed CO2 laser to irradiate the polyimide film to generate a laser-induced graphene electrode; wherein the laser power is 30W and the engraving depth is 30μm.
[0018] Optionally, the polyimide film further comprises the steps of ultrasonic cleaning with ethanol and drying before use.
[0019] A second aspect of the present invention is to provide a gas sensor for detecting NH3, which is prepared using the above preparation method.
[0020] The third aspect of the present invention is to provide a gas sensor for use in preparing a wearable flexible ammonia gas detection device.
[0021] The present invention has the following technical effects:
[0022] (1) The response time of the LIG@Cu3(HHTP)2 sensor to 50 ppm NH3 is 17 s at room temperature, which is much faster than most existing gas sensors.
[0023] (2) The LIG@Cu3(HHTP)2 sensor of the present invention can effectively distinguish NH3 from other interfering gases, such as benzene and H2S. The response value of 50 ppm NH3 is about 20 times higher than that of 50 ppm benzene and 50 ppm H2S.
[0024] (3) The LIG@Cu3(HHTP)2 sensor of the present invention maintains a response of approximately 4.8% to NH3 gas within 1000 s of repeated exposure to 50 ppm NH3, demonstrating good repeatability and high sensitivity to NH3.
[0025] (4) The present invention can operate normally without additional heat or light excitation, which simplifies the equipment configuration, reduces energy consumption, and improves portability and practicality;
[0026] (5) The present invention adopts laser direct writing technology, which can achieve flexible patterning and miniaturization of electrodes, making it possible to build large-scale, high-density sensor arrays and contributing to the development of multifunctional gas monitoring systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings, which constitute part of the present invention, are provided to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are provided to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0028] Figure 1 X-ray diffraction patterns of Cu3(HHTP)2-5Cycle prepared in Example 5, Zn3(HHTP)2 prepared in Comparative Example 1, and Ni3(HHTP)2 prepared in Comparative Example 2;
[0029] Figure 2 SEM images of the LIG electrode substrate prepared in Example 1 and LIG@Cu3(HHTP)2 prepared in Examples 1 to 6, where a is the LIG electrode substrate prepared in Example 1, and b to g are LIG@Cu3(HHTP)2 prepared in Examples 1 to 6, respectively;
[0030] Figure 3 Schematic diagram of the layer-by-layer preparation process of LIG@Cu3(HHTP)2 gas-sensitive material;
[0031] Figure 4 Actual images of the LIG@Cu3(HHTP)2 flexible gas sensors prepared in Examples 1 to 6, where 1C to 6C are Examples 1 to 6, respectively;
[0032] Figure 5 (a) is a photo of the LIG@Cu3(HHTP)2 flexible gas sensor prepared in Example 5, showing the structure of the MOF film, LIG, silver paste, and PI film; (b) is the constructed gas sensing test device; (c) is a diagram showing the bending of the element;
[0033] Figure 6 The response values of Cu3(HHTP)2 prepared in Example 5, Zn3(HHTP)2 prepared in Comparative Example 1, and Ni3(HHTP)2 prepared in Comparative Example 2 to 50 ppm of NH3 at room temperature;
[0034] Figure 7 Response values of LIG@Cu3(HHTP)2 prepared in Example 3 to 50 ppm of NH3, SO2, H2S, formaldehyde, toluene, and benzene at room temperature;
[0035] Figure 8 The dynamic response values of the LIG@Cu3(HHTP)2-xCycle sensors prepared in Examples 1 to 6 to 50 ppm NH3 at room temperature;
[0036] Figure 9 Response-recovery time curve of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to 50 ppm NH3 at room temperature;
[0037] Figure 10 This is the repeatability test curve of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to 50ppmNH3 at room temperature;
[0038] Figure 11 Dynamic response-recovery curve of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to 5-50 ppm NH3 at room temperature;
[0039] Figure 12 This is the linear fitting curve of the response of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to NH3 in the concentration range of 5-50 ppm;
[0040] Figure 13 Dynamic response-recovery curves of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 when exposed to 50 ppm NH3 at 0° and 10° bending angles at room temperature. DETAILED DESCRIPTION
[0041] The embodiment of the present invention discloses a method for preparing a gas sensor for detecting NH3, wherein a laser-induced graphene electrode is prepared on a polyimide film, and the laser-induced graphene electrode is alternately immersed in a copper ion solution and a HHTP ligand solution, and a layer-by-layer self-assembly process (such as Figure 3 (as shown) a metal organic framework Cu3(HHTP)2MOF is grown on the surface of the laser-induced graphene electrode, and a gas sensor based on a LIG@Cu3(HHTP)2 composite film is obtained after drying.
[0042] In some preferred embodiments, the copper ion concentration in the copper ion-containing solution is 1 mM; the concentration of the HHTP ligand solution is 0.1 mM. The copper ion is selected from copper acetate; the HHTP ligand is 2,3,6,7,10,11-hexahydroxytriphenylene; and the flexible substrate is selected from a polyimide film. The solvents for both the copper ion-containing solution and the HHTP ligand solution are ethanol, and both solutions are prepared under magnetic stirring at room temperature for 10 minutes.
[0043] In some preferred embodiments, the immersion temperature is 50°C; the immersion time for the copper ion solution and the HHTP ligand solution in each growth cycle is 20 minutes and 40 minutes, respectively. Each immersion step also includes a rinsing step with ethanol. Immersion in the copper ion solution, immersion in the HHTP ligand solution, and rinsing constitute one growth cycle, and the entire immersion process includes 1 to 6 growth cycles.
[0044] In some preferred embodiments, the drying is performed in an electric blower, the drying temperature is 60° C., and the drying time is 12 hours.
[0045] In some preferred embodiments, the width of the laser-induced graphene electrode is 0.5 mm, and the pitch / width ratio is 1:1.
[0046] In some preferred embodiments, the method for preparing the laser-induced graphene electrode is: using a pulsed CO2 laser to irradiate the polyimide film to generate a laser-induced graphene electrode; wherein the laser power is 30W and the engraving depth is 30μm.
[0047] In some preferred embodiments, the polyimide film further comprises the steps of ultrasonic cleaning with ethanol and drying before use. Specifically, the polyimide film is ultrasonically cleaned in ethanol for 10 minutes to remove dust and organic pollutants on the surface, and then rinsed with deionized water and dried.
[0048] The gas sensor for detecting NH3 prepared in the embodiment of the present invention has high sensitivity and fast response performance, is suitable for gas detection at room temperature, and has good flexibility and stability.
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] The raw materials used in the following examples and comparative examples were obtained from conventional commercial sources. Among them, copper acetate (Cu(CH3COO)2) was analytical grade; 2,3,6,7,10,11-hexahydroxytriphenylene (HHTP) was analytical grade; polyimide film (PI) was commercially available; ethanol and acetone were analytical grade; and deionized water was used.
[0055] It should be noted that the technical means not described in detail in the following examples and comparative examples can be operated using conventional technical means.
[0056] Example 1
[0057] A gas sensor based on a LIG@Cu3(HHTP)2 composite film, the preparation method comprising the following steps:
[0058] S1. A commercial polyimide (PI) film was used as a flexible substrate. The PI film was ultrasonically cleaned in ethanol for 10 minutes to remove surface dust and organic contaminants. The film was then rinsed with deionized water and dried.
[0059] S2. A CO2 laser was used to directly scribe a polyimide (PI) film to form interdigitated electrodes with a width of 0.5 mm and a pitch-to-width ratio of 1:1. Surface dust and organic contaminants were first removed with alcohol, followed by rinsing with deionized water and drying. A pulsed CO2 laser with an output power of 30 W and a wavelength of 10.6 μm was used to scribe to a depth of 30 μm. This laser induced layer-by-layer decomposition on the PI film surface, generating the LIG pattern.
[0060] S3. Accurately weigh 7.986 mg of copper acetate and 1.2971 mg of 2,3,6,7,10,11-hexahydroxytriphenylene (HHTP) to prepare a 1 mM Cu(II) solution. 2+ solution and 0.1 mM HHTP solution, and magnetically stirred at room temperature for 10 min to fully dissolve and evenly disperse the raw materials;
[0061] S4. The prepared LIG electrode substrate was alternately immersed in 1 mM Cu 2+ ions and 0.1mM HHTP ligand, with each immersion time of 20 minutes and 40 minutes respectively, and a growth cycle of 1 hour. After each growth cycle, LIG was cleaned with ethanol reagent to remove residual reactants. Then, silver paste was applied to the two pins of the LIG electrode to ensure firm contact between the LIG electrode and the copper wire connection. Finally, it was placed in a 60℃ electric blower for drying overnight to obtain a gas sensor based on LIG@Cu3(HHTP)2 composite material film, named LIG@Cu3(HHTP)2-1Cycle.
[0062] Example 2
[0063] A gas sensor based on LIG@Cu3(HHTP)2 composite film, the preparation method is the same as that of Example 1, except that in step S4, the prepared LIG electrode substrate is alternately immersed in 1 mM Cu2+ in 50°C ethanol solution. 2+ ions and 0.1mM HHTP ligand, with each immersion time of 20 minutes and 40 minutes respectively, and a growth cycle of 1 hour. After each growth cycle, LIG was washed with ethanol reagent to remove residual reactants. The above immersion and washing steps were repeated, that is, two growth cycles were performed. Then, silver paste was coated on the two pins of the LIG electrode to ensure firm contact between the LIG electrode and the copper wire connection. Finally, it was placed in an electric blower at 60℃ for overnight drying to obtain a gas sensor based on LIG@Cu3(HHTP)2 composite material film, named LIG@Cu3(HHTP)2-2Cycle.
[0064] Example 3
[0065] A gas sensor based on a LIG@Cu3(HHTP)2 composite material thin film is prepared by the same method as in Example 2, except that the growth cycles in step S4 are three. The resulting gas sensor based on the LIG@Cu3(HHTP)2 composite material thin film is named LIG@Cu3(HHTP)2-3Cycle.
[0066] Example 4
[0067] A gas sensor based on a LIG@Cu3(HHTP)2 composite material thin film is prepared by the same method as in Example 2, except that the growth cycles in step S4 are four. The resulting gas sensor based on a LIG@Cu3(HHTP)2 composite material thin film is named LIG@Cu3(HHTP)2-4Cycle.
[0068] Example 5
[0069] A gas sensor based on a LIG@Cu3(HHTP)2 composite material thin film is prepared by the same method as in Example 2, except that the growth cycles in step S4 are 5. The resulting gas sensor based on the LIG@Cu3(HHTP)2 composite material thin film is named LIG@Cu3(HHTP)2-5Cycle. Figure 1 is the X-ray diffraction pattern of Cu3(HHTP)2-5Cycle, Figure 1 The successful synthesis of the metal-organic framework Cu3(HHTP)2 can be confirmed.
[0070] Example 6
[0071] A gas sensor based on a LIG@Cu3(HHTP)2 composite material thin film is prepared by the same method as in Example 2, except that the growth cycles in step S4 are 6. The resulting gas sensor based on the LIG@Cu3(HHTP)2 composite material thin film is named LIG@Cu3(HHTP)2-6Cycle.
[0072] Comparative Example 1
[0073] A gas sensor based on a LIG@Cu3(HHTP)2 composite film was prepared by the same method as in Example 2, except that copper acetate was replaced with an equimolar amount of zinc acetate. The resulting gas sensor based on a LIG@Zn3(HHTP)2 composite film was named LIG@Zn3(HHTP)2-5Cycle. The X-ray diffraction pattern is shown in FIG. Figure 1 .
[0074] Comparative Example 2
[0075] A gas sensor based on a LIG@Cu3(HHTP)2 composite film was prepared using the same method as in Example 2, except that copper acetate was replaced with an equimolar amount of nickel acetate. The resulting gas sensor was named LIG@Ni3(HHTP)2-5Cycle and had an X-ray diffraction pattern of Figure 1 .
[0076] The scanning electron microscope (SEM) images of the LIG@Cu3(HHTP)2-xCycle sensors prepared in Examples 1 to 6 are shown in FIG. Figure 2 , where the framed part is a local enlarged view. Figure 2 It can be seen that in the first growth cycle, Cu3(HHTP)2 nanocrystals initially nucleated and grew on the LIG surface. The crystals were small in size and sparsely distributed, and the original 3D porous structure of LIG was visible in some areas. In the sixth growth cycle, the Cu3(HHTP)2 nanocrystals grew fully, increased in size, and became more regular in shape, forming a porous network structure that evenly covered the LIG surface. These SEM images show that with increasing immersion time, Cu3(HHTP)2 grew more fully on LIG, forming a porous network structure. This structure helps to improve the adsorption of gas molecules, thereby enhancing the performance of the sensor. Consistent with the rapid response mentioned in the project, it shows that extending the immersion time helps to optimize the microstructure of the sensor, thereby improving its gas-sensing performance.
[0077] The physical pictures of LIG@Cu3(HHTP)2-xCycle sensors prepared in Examples 1 to 6 are shown in Figure 4 ,Depend on Figure 4 It can be seen that with the increase of growth cycles, the color of the sensor surface gradually deepens and the thickness of the metal-organic framework layer increases.
[0078] The performance test of the gas sensors prepared in Examples 1 to 6 was carried out as follows:
[0079] Build as Figure 5The gas sensing test setup shown in Figure (b) installs the prepared LIG@Cu3(HHTP)2 gas sensor in a gas test chamber and connects it to a data acquisition system. Before testing, air is introduced and the system is allowed time to stabilize, typically 5-10 minutes. During this time, the sensor's output signal is continuously monitored until it stabilizes before conducting subsequent gas tests. A specific volume and concentration of gas is injected into the test chamber via a syringe (the amount of injected gas is precisely controlled based on the sensitivity of the detection system and the detection requirements). The principle of ammonia detection is that upon entering the detection system, ammonia reacts chemically with the Cu3(HHTP)2 surface material of the sensor's gas-sensing element, causing a change in its resistance. Specifically, NH3 molecules interact with the mixed-valence Cu ions in Cu3(HHTP)2, altering the carrier concentration of Cu3(HHTP)2 and, in turn, causing a change in resistance. Based on the electrical signals generated by these reactions, the detection system monitors key parameters such as the gas resistance change, response time, recovery time, and sensor sensitivity in real time. Environmental conditions (such as temperature, pressure, and humidity) and experimental operating conditions (such as injection volume, injection speed, and dilution factor) were also recorded to facilitate analysis and evaluation of the test results. The sensor response is defined as S = ΔR / R0 × 100%, where ΔR = Rg - R0; Rg and R0 represent the sensor resistance in ammonia and air, respectively. Gas-sensing performance testing included response-recovery curve testing, dynamic response testing at varying ammonia concentrations, selectivity testing, and repeatability testing. All tests were performed at room temperature.
[0080] Figure 6 The response values of LIG@Cu3(HHTP)2-5Cycle prepared in Example 5, LIG@Zn3(HHTP)2-5Cycle prepared in Comparative Example 1, and LIG@Ni3(HHTP)2-5Cycle prepared in Comparative Example 2 to 50 ppm NH3 at room temperature are shown in Table 1. Figure 6 It can be seen intuitively that the response of Cu3(HHTP)2 to NH3 gas is the highest among the three materials, which shows that Cu3(HHTP)2 has higher sensitivity and specific recognition ability for NH3, and has better selectivity than Zn3(HHTP)2 and Ni3(HHTP)2. At the same time, when Cu3(HHTP)2 is combined with laser-induced graphene (LIG), it can form a composite material with a hierarchical pore structure. LIG provides good conductivity and porous structure, while Cu3(HHTP)2 has a large specific surface area and uniform pore size distribution, which enhances the adsorption and reaction activity of NH3 molecules. This synergistic effect makes the gas sensor of LIG@Cu3(HHTP)2 composite film have more excellent gas sensing performance at room temperature.
[0081] Figure 7 The response values of LIG@Cu3(HHTP)2-3Cycle prepared in Example 3 to 50 ppm of NH3, SO2, H2S, formaldehyde, toluene and benzene at room temperature are given by Figure 7 It can be seen that the LIG@Cu3(HHTP)2-3Cycle prepared in Example 3 has the highest dynamic response value to 50 ppm NH3 at room temperature. Therefore, the LIG@Cu3(HHTP)2-3Cycle prepared in Example 3 has good selectivity for ammonia and is suitable for the detection of NH3.
[0082] Figure 8 The dynamic response values of the LIG@Cu3(HHTP)2-xCycle sensor prepared in Examples 1 to 6 to 50ppmNH3 at room temperature; Figure 8 It can be seen that when the growth cycle is 5, the dynamic response value of Example 5 is the highest and the sensitivity is the best. Therefore, the sensor of Example 5 was selected for subsequent testing.
[0083] Figure 9 Response-recovery time curve of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to 50ppmNH3 at room temperature; Figure 9 It can be seen that the response time of the sensor to 50ppmNH3 is only 17s, and the recovery time is only 36s. The fast response speed is conducive to shortening the detection cycle.
[0084] Figure 10 This is the repeatability test curve of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to 50ppmNH3 at room temperature; Figure 10 It can be seen that the sensor still has an excellent dynamic response value after 5 cycles, that is, the sensor has good repeatability and stability.
[0085] Figure 11 The dynamic response-recovery curve of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to 5-50ppm NH3 at room temperature; Figure 11 It can be seen that the sensor still has the ability to detect 5 ppm of NH3 at room temperature with a low detection limit, which shows that the sensor is particularly suitable for detecting ammonia.
[0086] Figure 12 This is the linear fitting curve of the response of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 to NH3 in the concentration range of 5-50 ppm. It can be seen that the sensor has good linearity in the concentration range of 5-50 ppm.
[0087] Figure 13 The dynamic response-recovery curves of the LIG@Cu3(HHTP)2-5Cycle sensor prepared in Example 5 when exposed to 50ppmNH3 at 0° and 10° bending angles at room temperature show that the sensor has good flexibility and is particularly suitable for wearable and portable detection devices.
[0088] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A method for preparing a gas sensor for detecting NH3, characterized in that: A laser-induced graphene electrode was prepared on a polyimide film, which was alternately immersed in a copper ion solution and an HHTP ligand solution. A metal-organic framework was grown on the surface of the laser-induced graphene electrode through layer-by-layer self-assembly. After drying, a gas sensor based on a LIG@Cu3(HHTP)2 composite film was obtained.
2. The method for preparing a gas sensor for detecting NH3 according to claim 1, wherein: The copper ion concentration in the copper ion-containing solution is 1 mM; and / or the concentration of the HHTP ligand solution is 0.1 mM.
3. The method for preparing a gas sensor for detecting NH3 according to claim 1, wherein: The immersion temperature is 50° C.; and / or, the immersion time of the copper ion solution and the HHTP ligand solution is 20 minutes and 40 minutes respectively.
4. The method for preparing a gas sensor for detecting NH3 according to claim 3, wherein: After each immersion is completed, the method further comprises a step of washing with ethanol; and / or the number of alternating immersions is 1 to 6 times.
5. The method for preparing a gas sensor for detecting NH3 according to claim 1, wherein: The drying temperature is 60° C., and the drying time is 12 h.
6. The method for preparing a gas sensor for detecting NH3 according to claim 1, wherein: The width of the laser-induced graphene electrode is 0.5 mm, and the pitch / width ratio is 1:
1.
7. The method for preparing a gas sensor for detecting NH3 according to claim 1, wherein: The preparation method of the laser-induced graphene electrode is as follows: using a pulsed CO2 laser to irradiate the polyimide film to generate a laser-induced graphene electrode; wherein the laser power is 30W and the engraving depth is 30μm.
8. The method for preparing a gas sensor for detecting NH3 according to claim 1, wherein: The polyimide film further comprises the steps of ultrasonic cleaning with ethanol and drying before use.
9. A gas sensor for detecting NH3, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the gas sensor according to claim 9 in preparing a wearable flexible NH3 gas detection device.